Application and analysis of direct sampling method in real-world microwave imaging. (October 2019) - Son, Seong-Ho; Lee, Kwang-Jae; Park, Won-Kwang
Abstract: In this paper, a direct sampling method (DSM) is designed for a real-time detection of small anomalies from scattering parameters measured by a small number of dipole antennas. Applicability of the DSM is theoretically demonstrated by proving that its indicator function can be represented in terms of an infinite series of Bessel functions of integer order, Hankel function of order zero, and the antenna configurations. Experiments using real-data then demonstrate both the effectiveness and limitations of this method.